A newly recorded Subgenus Sudila from China with description of two new species (Hymenoptera: Halictidae: Lasioglossum) - Zhang, Rui; Li, Qiang; Niu, Ze-Qing; Zhu, Chao-Dong (Zootaxa, 2011)
The subgenus Sudila (Cameron, 1898) is reported from China for the first time. Lasioglossum (Sudila) genotrigonum Zhang et Zhu, sp. nov. and L. (S.) semiruginosum Zhang et Zhu, sp. nov. are described and illustrated.